Telaah Al-Siyasah Al-Ahkam Al-Usrah Terhadap UUP No. 1 Tahun 1974 - Putra, Abdur Rahman Adi Saputera (El-Ahli : Jurnal Hukum Keluarga Islam, 2020)
Abstract Islamic law is one of the important instruments that cannot be denied its existence and validity in Indonesia, history clearly records that its emergence was not just spontaneity, but was also colored by the tidal process of political struggle between Islamic intellectuals and state elites at the time, not with the exception of Law No. 1 of 1974 concerning Marriage which in memorandum bene is also in the vortex of the transformation. Al-Siyasah Al-Ahkam Al-Usrah or Islamic family law politics, is a process of achieving the vision and aspiration to form a "national" marriage law, in fact it has been initiated since 1950. In the past renewal of marriage law has always met with failure due to Subjects and objects governed by marriage law are closely related to social and religious life, which are not easy to integrate. This means that the renewal of the national marriage law must be done carefully, so as not to cause disappointment for other groups of the population. The formation of the Marriage Law has a very long process and is then deliberated seriously with the contents of the Draft Law on Marriage, so that it can accommodate the aspirations of the people and provide a technically juridical formulation, and all this again is inseparable from the political atmosphere and intervention that occurred at that time. Keywords: Al-Siyasah, Al-Ahkam, Al-Usrah, UUP No. 1 of 1974